From Fiction to Fact. Comparing Media Portrayals of Climate Change and California Wildfires - Sonego, Allegra (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
This paper explores the role of entertainment and news media in shaping public perception of climate change, with a specific focus on the 2018 California wildfires. While traditionally the news media have been the primary conduit for communicating climate-related information, the study highlights the increasing importance of entertainment television in depicting environmental issues. By analyzing episodes of the popular TV series Station 19 (ABC, 2018-present) alongside international news coverage, the research investigates how visual narratives, thematic frameworks, and storytelling techniques converge to portray the intersection of climate change and natural disasters. Through a qualitative analysis of news broadcasts and f ictional representations, the study reveals a complex interplay between dramatization and factual reporting, underscoring the potential of both mediums to influence public understanding. Key findings suggest that while news media tend to emphasize immediate human suffering and quantitative data, fictional series offer a more intimate, humanized portrayal of environmental crises. However, both forms often neglect to engage deeply with the broader environmental and climate-related context. The paper concludes by advocating for more balanced media narratives that integrate both the human impact and ecological causes of disasters, encouraging public discourse on climate change and disaster prevention strategies.